STEAM and Writing Creativity: A Systematic Review with Implications for Higher Education - Lestari, Dewi; Abdurrahman; Maydiantoro, Albert; Kadaryanto, Budi; Setiyadi, Bambang (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2026)
This study synthesizes how Science, Technology, Engineering, Arts, and Mathematics (STEAM)-oriented learning has been linked to writing creativity and literacy development, with particular attention to the transferability of these practices to higher education.  A systematic review guided by PRISMA was conducted using Scopus and Web of Science. Searches covering 2017–2025 yielded 200 records. After 32 duplicates were removed, 168 records were screened by title and abstract, 50 full-text articles were assessed for eligibility, and 10 studies were included in the final qualitative synthesis.The analysis used a structured extraction matrix and qualitative content analysis to identify recurring instructional mechanisms, writing outcomes, enabling conditions, and constraints.  The review found four recurring pedagogical mechanisms: multimodal digital storytelling, project-based design and documentation, collaborative inquiry supported by reflective writing, and scaffolded argumentative or expository composition. Across the reviewed sources, the most frequent writing-related outcomes were general literacy or communication development (n = 5), multimodal or digital writing (n = 4), argumentative or expository writing (n = 4), and creative, reflective, and disciplinary writing outcomes (each n = 3). The evidence base also indicates several implementation constraints, particularly uneven educator readiness, time-intensive project structures, and   unequal access to digital infrastructure. Although direct higher education studies remain limited, the reviewed literature consistently suggests that STEAM-rich environments can increase students’ engagement, idea generation, organization of written explanations, and willingness to revise. The review concludes that STEAM should be understood not only as an   interdisciplinary   content   framework   but   also   as   a   literacy-rich pedagogical ecology that can strengthen academic writing when adapted deliberately to university contexts.